Effects of nicotinic acid on endothelial cells and platelets - Stach-Jablonski, Ksenija; Zaddach, Friederike Anita; Nguyen, Xuan-Duc; Elmas, Elif; Kralev, Stefan Borissov; Weiß, Christel; Borggrefe, Martin; Kälsch, Thorsten (Cardiovascular pathology, 2012)
Background: Interactions between platelets and endothelial cells under inflammatory conditions lead to an increased expression of various activity markers of atherosclerosis in the vessel wall. The purpose of this study was to investigate possible protective effects of nicotinic acid in an in vitro endothelial cell model. Methods: After a 24-hour incubation period with nicotinic acid (1 mmol/l), human umbilical vein endothelial cells were stimulated for 1 h with lipopolysaccharide and were then incubated in direct contact with activated platelets. Following this incubation, the expression of CD40L and CD62P on platelets and the expression of intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1, uPAR, and MT1-MMP on endothelial cells were measured by flow cytometry. Supernatants were analyzed by ELISA for soluble MCP-1 and MMP-1. Results: The increased expression of VCAM-1 on endothelial cells by proinflammatory stimulation with activated platelets was significantly reduced through preincubation with nicotinic acid (P<.05). Furthermore, platelets in direct contact with preincubated endothelial cells showed a significant reduction in their CD62P and CD40L expression when compared to platelets incubated with untreated endothelial cells (P<.05). Treatment with nicotinic acid did not have a significant effect on ICAM-1, uPAR, and MT1-MMP expression on endothelial cells. Levels of soluble MCP-1 and MMP-1 in supernatants were lower after preincubation with nicotinic acid. Conclusion: Nicotinic acid inhibits platelet activation after platelets contacted nicotinic acid treated endothelial cells and inhibits VCAM-1 expression on human endothelial cells under inflammatory conditions. These findings suggest a possible pleiotropic therapeutic relevance of nicotinic acid in atherosclerosis.